Determinants of troponin T and I elevation in old patients without acute coronary syndrome - Antonio Di Micoli; Chiara Scarciello; Stefania De Notariis; Mario Cavazza; Antonio Muscari (Emergency Care Journal, 2019)
Cardiac troponins T and I (cTnT and cTnI) are the main markers of acute myocardial cell damage and then of Acute Coronary Syndrome (ACS) if associated with compatible symptoms. Although their cardio-specificity, the cTn may be increased in various clinical conditions but only few recent studies have reported their trends with age. This is a single-center retrospective observational study on two groups of adults consecutive patients, with age ≥65 years, admitted to the Emergency Department of the Sant'Orsola-Malpighi Hospital of Bologna, Italy, with chest pain as chief complaint. In the first group was dosed cTnT (N=617), in the second group cTnI (N=569). The patients with final ACS’s diagnosis (N=255) or an incomplete report of blood tests (N=17) were excluded. The definitive database included 471 patients in the first group and 443 in the second one. The observed differences between clinical parameters, patients with cTnT≤14ng/L and those with cTnT>14ng/L (N=207, 44%) are: older age, greater prevalence of diabetes, lower values of Hb e ALT, higher values of white blood cells, INR, glycemia, urea, creatinine, BNP e PCR. In multiple logistics regression (N=333) only 4 variables resulted independently associated to cTnT increase: age (P<0.0001), PCR (P=0.01), creatinine (P=0.02) and urea (P=0.04), R2=0.30. The differences between patients with cTnI≤40ng/L and those with cTnI>40ng/L (N=46, 10%) are: older age, Hb values equal and higher values of white blood cells, INR, glycemia, urea, creatinine, total bilirubin, AST, BNP e PCR. In multiple logistics regression (N=259) the only 4 variables independently associated to increase of cTnI are age (P<0.0001), glycemia (P=0.004), PCR (P=0.01) and white blood cells (P=0.02), R2=0.17. Furthermore, the number of patients with high level of cTn significantly increase by age (cTnT: 65-74 years 22.2%, 75-84 years 48.5%, ≥85 years 79.5%; cTnI: 65-74 years 4.3%, 75-84 years 8.1%, ≥85 years 22.5%, P<0.0001). In our study, cTnI showed fewer false positives than cTnT and seems to be less influenced by kidney failure. Furthermore, the acute phase of inflammation was associated with the rise of troponins. High cTn values were found in elderly subjects, without acute coronary syndromes, particularly cTnT. Then the age seems to be the most important factor related to this highelevated troponin levels.